Knowledge and attitude towards HIV/AIDS in Pakistan, a systematic review - Sarmad Javed; Saim Amir; Zain Tariq; Gul Sher Ghouri; Shamaim Naeem; Muhammad Zain; Fatmeen Athar; Sheraz Ali; Hira Aamer; Waseem Sajjad (Discover Public Health)
Abstract Background and objectives As of June 2019, Pakistan’s National AIDS Control Program (NACP) reported 24,331 registered patients, estimating around 165,000 infections. HIV’s prevalence is shaped by demographics, social norms, cultural attitudes, limited awareness, and disease stigma. This systematic review aims to identify the knowledge and attitude of the people living in Pakistan towards HIV/AIDS, as little work has been published in this field. Materials and methods The search was conducted according to PRISMA guidelines using PubMed and Google Scholar electronic databases. This systematic review includes all the observational studies, cross-sectional studies and surveys that reported data about the knowledge and attitude towards HIV/AIDS in any target population in Pakistan, published from 2010 to 2023. PROSPERO ID: CRD42023469834. Results Among the 17 included studies (n = 4,889), 41.2% reported good knowledge and only 17.6% showed a positive attitude toward people living with HIV. Knowledge was higher among medical populations, while attitudes remained largely negative across all groups. Urban residency, education, and HIV training were associated with better outcomes. These findings highlight a persistent gap between knowledge and empathetic attitudes in Pakistan, suggesting an urgent need for targeted awareness campaigns. Conclusion The poor knowledge and insufficient attitude towards HIV/AIDS in Pakistan are concerning and should be catered to. This impedes attempts at efficient prevention and treatment. Education and awareness campaigns need to be strengthened to debunk myths and encourage preventive health care.